The KCNA book : pass the Kubernetes and cloud native associate exam in style - Poulton, Nigel (Telecommunications engineer) (Packt Publishing, 2022)
Boost your knowledge with the well-organized revision guide for Kubernetes and Cloud Native Associate (KCNA) certification and exam. Expand your horizon of possibilities with extensive explanations and quizzes Key Features Learn new technologies and revise concepts to master the KCNA certification and exam Reinforce and test knowledge through practice questions and an exam Boost your career by leveraging Kubernetes and cloud-native technologies Book Description There is a huge benefit in building small, specialized, single-purpose apps that can self-heal, auto scale, and update regularly without needing downtime. Kubernetes and cloud-native technologies come in handy in building such apps. Possessing the knowledge and skills to leverage Kubernetes can positively enhance possibilities in favor of architects who specialize in cloud-native microservices applications. 'The KCNA Book' is designed to help those working in technology with a passion to become certified in the Kubernetes and Cloud-Native Associate Exam. You will learn about containerization, microservices, and cloud-native architecture. You will learn about Kubernetes fundamentals and container orchestration. The book also sheds light on cloud-native application delivery and observability. It focuses on the KCNA exam domains and competencies, which can be applied to the sample test included in the book. Put your knowledge to the test and enhance your skills with the all-encompassing topic coverage. Upon completion, you will begin your journey to get the best roles, projects, and organizations with this exam-oriented book. What you will learn Learn the essentials of containerization and microservices Know about cloud-native architecture and autoscaling Gain clarity about container orchestration Master the fundamentals of Kubernetes Explore cloud-native application delivery and observability Become competent in the KCNA exam domains Who this book is for 'The KCNA Book' is crafted for anyone working in technology. It is specifically helpful for those wishing to gain the KCNA certification. The KCNA exam is designed to test proficiency in Kubernetes and cloud-native skills and concepts. It is well-suited for architects, developers, data engineers, and anyone from a traditional IT background. The KCNA exam and certification is particularly useful in the field of management, technical marketing, operations, DevOps, CloudOps, SREs, and DevSecOps.